KREATIVITAS GURU DALAM MENINGKATKAN PENGUASAAN ILMU TAJWID SISWA DI TPA AL-MUKMININ BASE CAMP KABUPATEN PASAMAN BARAT - Elinda Safitri; Irna Adriati; Arifmiboy Arifmiboy; Charles Charles (KOLONI, 2022)
From the problems that exist, researchers are interested in examining how the form of teacher creativity in using learning methods to improve students' ability to master the law of tajwid and makharijul letters. This type of research is field research with a field approach that describes the phenomena that occur in the field. Researchers conducted research at the Base Camp, Kinali District, West Pasaman Regency. In this study, the key informants were the teachers who taught at the Al-mukminin TPA and the supporting informants were the students who were studying at the Al-mukminin TPA. To collect data, the writer uses observation, interview and documentation techniques. In analyzing the data, the writer analyzes the data using a qualitative descriptive method. And to test the validity of the data obtained by the author using data trigulation. As for the results of the research that has been done, it can be concluded that teachers at TPA Al-mukminin have tried to develop their creativity in terms of learning methods to improve students' ability to master the science of recitation. The teacher creates several methods used such as jibril, iqra, lectures, question and answer and the teacher also creates it with a new method, namely the card matching method in which students are asked to use the lafaz card method which is given with the tajwid law on the card and students who answer correctly are given rewards. . The low mastery of students' tajwid is caused because some students do not focus on learning and some students also do not repeatedly read the Qur'an at home. Keywords: Teacher Creativity, Tajweed Science, Students